EFEKTIVITAS PELAKSANAAN PROGRAM SEKOLAH ADIWIYATA DI SMA NEGERI 15 KOTA PADANG - Arin Wiwin Diana; Adil Mubarak (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The Adiwiyata school program in the city of Padang, especially at SMA Negeri 15 Padang, has actually been going on since 2013, but in reality there is still low awareness of environmental care from the point of view of the school community, especially students and other devices, this can be proven that the school is still not clean and does not throw garbage yet. in place. This study aims to determine the implementation and effectiveness of the Adiwiyata school program implemented at SMA Negeri 15 Padang. This study uses the theory of successful implementation of a program (According to Weimer 7 Vinning: 2009) and the theory of effectiveness according to Budiani in (Amelia, 2015) then this research is descriptive using qualitative methods. The data collection technique is done by interview, observation, documentation study so that accurate conclusions are drawn from the data that has been obtained. The results showed that the implementation of the Adiwiyata school program implemented in SMA Negeri 15 Padang was quite effective but not 100%. This was evidenced by the lack of clarity regarding the prospects of this program in writing at SMA Negeri 15 Padang